These are very hard to read as you keep forgetting plus and minus signs! But your logic is fine. The first is correct. The second is not.
You are correct up to , now subtract from both sides to find .
The First One: 8(5-3x)-4(2+3x)=3
Expansion: -24x -12x 40-8 =3
Combine:-36x 32 =3
Shift: -36x = 3-32= -29
Solution: x= -29/-36
The Second One: 9(1+x)-8(x+2)= 2x
Expansion: 9x-8x 9-16 =2x
Combine: x -7 =2x
Shift: (x-2x) -7= 2x -2x
-x = -7
Solution: x= -7/-1
Is my formula for solving these equations correct (there are other ways but I thought my method is the easiest, or am I wrong?)? And are my solutions correct? If they're wrong, could you show me where I went wrong? Thanks guys!